Fuzzy modeling and bayesian inference network (Informatică economică, 2007)
Data mining is an evolving and growing area of research and involves interdisciplinary research and development encompassing diverse domains. In this age of multimedia data exploration, data mining should no longer be restricted to the mining of knowledge from large volumes of high-dimensional data sets in traditional databases only. The aim of the paper is to present guidelines in fuzzy modeling, fuzzy clustering and the design of Bayesian inference networks